2001
DOI: 10.1034/j.1399-6576.2001.450807.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lignocaine 2% with adrenaline, bupivacaine 0.5% with or without hyaluronidase and a mixture of bupivacaine, lignocaine and hyaluronidase for peribulbar block analgesia

Abstract: All four agents provided adequate analgesia during cataract extraction lasting approximately 95-100 min after PBA injection. Lido 2% epi demonstrated most rapid onset and required least number of injections to establish block. A hyaluronidase effect was evident only after 15 min in the bup 0.5% hyalase and lido/bup/hyalase groups. Bup 0.5% plain was overall the least satisfactory, and the greatest supplementation rate occurred with lido/bup/hyalase, suggesting that either lido 2% epi or bup 0.5% hyalase are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…The onset of complete block was more rapid in the atracurium group in this study compared with the control group and to the previous studies. [7][8][9] Twenty-nine patients of group II achieved an akinesia score of zero in this study. This finding is in agreement with the results of Reah's previous work.…”
Section: Discussionmentioning
confidence: 72%
“…The onset of complete block was more rapid in the atracurium group in this study compared with the control group and to the previous studies. [7][8][9] Twenty-nine patients of group II achieved an akinesia score of zero in this study. This finding is in agreement with the results of Reah's previous work.…”
Section: Discussionmentioning
confidence: 72%
“…After instillation of three to four drops of amethocaine 1% into the conjuctival sac of the appropriate eye, the two‐injection inferolateral‐superomedial peribulbar anaesthesia technique described by Hamilton [20], rather than his inferolateral‐nasal technique, was performed using a 15 mm, 25 mm or 37.5 mm 25G needle. The local anaesthetic mixture used in the hospital, which comprises a 2 : 3 volume mixture of lidocaine 2% and bupivacaine 0.5%, without epinephrine but with added hyaluronidase 25 iu.ml −1 (Wydase, Wrexham Pharmaceuticals, Wrexham, England), was used for all primary and supplementary injections [18]. Injections were performed at a rate of 0.2 ml.s −1 until mild proptosis occurred.…”
Section: Methodsmentioning
confidence: 99%
“…He insists on performing the sub‐Tenon's injection himself. The sub‐Tenon's technique has not been adopted by any of the seven anaesthetists in the hospital, all of whom prefer conventional peribulbar anaesthesia [1, 15–18]. Furthermore, no consensus view exists amongst the anaesthetists, who all have extensive experience of eye blocks for ophthalmic surgery, as to which length of needle is the most effective in producing peribulbar blockade.…”
mentioning
confidence: 99%
“…Van Den Berg and Montoya-Pelaez12 showed that the addition of hyalase improved akinesia compared with plain bupivacaine, but lidocaine plus epinephrine was superior in providing complete akinesia with the lowest number of top-up injections.…”
Section: Hyaluronidasementioning
confidence: 99%